Validation of a TLP wind turbine numerical model against model-scale tests under regular and irregular waves. (15th July 2022) - Vardaroglu, Mustafa; Gao, Zhen; Avossa, Alberto Maria; Ricciardelli, Francesco
Abstract: Higher capacity factors compared to the onshore wind, decreasing cost of energy make floating wind turbines a powerful source of carbon-free energy future. Response of floating wind turbines can be observed over numerical analyses and physical model tests. In this study, the dynamic response of a TLP FWT numerical model is investigated under regular and irregular waves and compared with a scaled physical model. Open-source numerical tools are utilized in the time-domain and frequency domain. The comparison of the full-scale responses between the numerical and the experimental results are based on the use of measured waves as input to the numerical model to reduce the uncertainties in the wave simulations. Hydrodynamic damping in the numerical model is tuned according to the decay tests on the scaled physical model. Overall, close estimations of the physical model motion response, tendon tensions, and tower base moments are obtained over the comparisons of time histories, RAO, and statistics. Uncertainties in the physical model measurements and the limits of the numerical model are discussed. Highlights: TLPs are ideal for deep waters with high tendon stiffness and low motion responses. Numerical modeling of a TLP wind turbine by using open-source tools. Numerical model hydrodynamic damping is calibrated according to the physical model. Numerical and physical model responses are compared under wave-induced loading. Uncertainties in the physical model and limits of the numerical model are highlighted.